Birjand longitudinal aging study (BLAS): the objectives, study protocol and design (wave I: baseline data gathering) - Moodi, Mitra; Firoozabadi, Mohammad Dehghani; Kazemi, Tooba; Payab, Moloud; Ghaemi, Kazem; Miri, Mohammad Reza; Sharifzadeh, Gholamreza; Fakhrzadeh, Hosein; Ebrahimpur, Mahbube; Arzaghi, Seyed Masoud; Zarban, Asghar; Mirimoghadam, Ebrahim; et al. (Journal of diabetes and metabolic disorders, 2020)
Objectives The pace of population aging is growing rapidly around the world. Aging is associated with the emergence of different health status including geriatric syndrome such as frailty, diabetes, cardiovascular diseases, and dementia. These conditions are the most prominent challenges for health care systems and also elderly people. Therefore, understanding these changes can help scientists to prevent and treat significant health issues and also improve the functional ability of older adults. Methods This is a protocol of the first wave of Birjand Longitudinal Aging Study that is an ongoing community-based prospective cohort study with a following up at least 10 years. This study carries out on aged population ≥ 60 years which were residents in Birjand County (urban and rural older subjects). The selection of the participants of this study in urban areas is based on an age group weighted multistage stratified random sample while in the rural region the sample was selected from all ten rural regions of Birjand County by simple random sampling. The rural region sampling was based on the list of the aged population which were under the coverage of the rural health center. Sociodemographic, past medical history, lifestyle, sleep, activities of daily living, cognitive function, quality of life, and social capital were evaluated by interviewing with the participants and one of the informants. Anthropometric measures, electrocardiography, and interpretation of ophthalmologic examination were carried out by experts. Fasting Blood samples were collected and bio-banked in − 80 °C. then finally biochemical and hematologic markers were measured. Results This is the protocol of stage one baseline of Birjand Longitudinal Aging Study (BLAS). The BLAS is an enjoining study, the first phase of its baseline was carried out on a community- dwelling aged population sample ≥ 60 years who were residents in urban and rural regions of Birjand County. This is a community based prospective cohort study with at least 10 years follow up of participants. The data for 65% of older subjects (response rate = 65%) that lived in clusters were collected. Conclusions This study can help scientists to recognize some risk factors related to the aging process and also aware policymakers about the necessity to create heath care services at regional and even national levels.